2021
DOI: 10.3389/fphys.2021.752144
|View full text |Cite
|
Sign up to set email alerts
|

Time Course and Role of Exercise-Induced Cytokines in Muscle Damage and Repair After a Marathon Race

Abstract: Endurance exercise induces an increase in the expression of exercise-induced peptides that participate in the repair and regeneration of skeletal muscles. The present study aimed to evaluate the time course and role of exercise-induced cytokines in muscle damage and repair after a marathon race. Fifty-seven Brazilian male amateur marathon finishers, aged 30–55 years, participated in this study. The blood samples were collected 24 h before, immediately after, and 24 and 72 h after the São Paulo International Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…Previous study of our group demonstrated a reduction of myostatin 3 days after the race which may contribute to muscle repair after exercise and a decrease of apelin and musclin in the same period (de Sousa et al, 2021). The role of these changes on muscle repair remains unclear and should be investigated.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Previous study of our group demonstrated a reduction of myostatin 3 days after the race which may contribute to muscle repair after exercise and a decrease of apelin and musclin in the same period (de Sousa et al, 2021). The role of these changes on muscle repair remains unclear and should be investigated.…”
Section: Discussionmentioning
confidence: 82%
“…Exercise-induced cytokines may be released by myocytes, satellite cells, endothelial cells, hepatocytes, residential macrophages, and fibroblasts, affecting skeletal and cardiac muscle as well as blood vessels, adipose tissue and brain (Hoffmann and Weigert, 2017;Lee and Jun, 2019;Laurens et al, 2020). Recently, our group demonstrated the increase of brain-derived neurotrophic factor (BDNF), fibroblast growth factor 21 (FGF-21), follistatin (FSTL) and decorin, as well as a decrease of myostatin, musclin and apelin after the race (de Sousa et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests an altered FGF-21 signaling during cardiovascular disease, which might also occur in sCVD patients. Studies examining the acute effects of exercise on FGF-21 have presented conflicting results, ranging from an increase of FGF-21 following whole-body exercise in healthy individuals ( de Sousa et al, 2021 ; Domin et al, 2021 ; Jurimae et al, 2021 ), small FGF-21 changes in obese subjects and even lower FGF-21 in older men ( Taniguchi et al, 2016 ; Khalafi et al, 2021 ). The local handgrip exercise bout performed in our study makes it difficult to compare our results with these previous studies that have typically adopted whole-body exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Very likely, production of myokines in skeletal muscle follows a diurnal rhythm 63 . Moreover, exercise‐induced release of myokines such as IL‐6 is highest immediately after exercise and levels off in the subsequent 72 h 64 . Currently, it is unknown if this timed release of mykokines depends on the time of day when exercise is performed.…”
Section: Mechanisms Linking Exercise and Metabolic Adaptationmentioning
confidence: 99%